La organización gremial del Trabajo Social en el Valle del Cauca, Caldas y Bogotá: análisis histórico-crítico - Nora Liliana Guevara Peña; Sergio Andrés Quintero Londoño; Ricardo Plazas Neisa (Eleuthera)
This article attempts to account for the emergence and development of three trade associations in Colombia, the Association of Social Workers of the Valley, the Association of Social Workers of Caldas and the Association of Social Work Graduates of Bogotá and the Region, within the framework of the development of the capitalist mode of production from the 1950s to the present. Methodology. A qualitative socio-historical analysis is carried out based on the analysis of more than 4,000 files from the associations and semi-structured interviews, triangulation was made between the theoretical-methodological foundations of the Marxist tradition, the information collected and the contrast with the stories. Results. With the analysis of the historical processes of the three associations, common interests and modernizing ideas are identified in them regarding working conditions, defense of Social Work, professional training and research, as well as a need for critical professional renewal.